Construction of three foot-and-mouth disease virus peptide phage display libraries as a tool for the identification of important epitopes - Chitray, Melanie (University of Pretoria, 2023)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2023.